Effect of Al Addition on the Oxidation Resistance of HfC Thin Films; Coatings; Vol. 12, iss. 1 - Gaydaychuk A. V. Alexander Valerievich; Linnik S. A. Stepan Andreevich; Mitulinsky A. S. Aleksandr Sergeevich; Zenkin S. P. Sergey Petrovich (2022, 2022)
Title screen